Family-led rehabilitation after stroke in India: a randomised controlled trial - Lindley, Richard; Anderson, Craig S.; Billot, Laurent; Forster, Anne; Hackett, Maree L.; Harvey, Lisa A.; Jan, Stephen; Li, Qiang; Liu, Hueiming; Langhorne, Peter; Maulik, Pallab K.; Murthy, Gudlavalleti Venkata Satyanarayana; et al. (Elsevier, 2017)
Background: Most people with stroke in India have no access to organised rehabilitation services. The effectiveness of training family members to provide stroke rehabilitation is uncertain. Our primary objective was to determine whether family-led stroke rehabilitation, initiated in hospital and continued at home, would be superior to usual care, in a low resource setting. Methods: The Family-led Rehabilitation after Stroke in India (ATTEND) trial was a prospectively randomised open trial with blinded endpoints (PROBE) conducted across 14 hospitals in India. Patients (and their caregivers) were randomised to intervention or usual care by site Coordinators, using a secure web-based system, with minimisation by site and stroke severity. The intervention group received additional structured rehabilitation training, commenced in hospital and continued at home for up to 2 months. The primary outcome was death or dependency, defined by scores 3 to 6 on the modified Rankin scale (range, 0 [no symptoms] to 6 [death]) as assessed by blinded observers at six months. Secondary outcomes included any serious adverse event, hospital length of stay, activities of daily living, health-related quality of life, anxiety and depression, and caregiver strain. All analyses were intention to treat. Registration: Clinical Trials Registry-India (CTRI/2013/04/003557); Australian New Zealand Clinical Trials Registry (ACTRN12613000078752); and Universal Trial Number (U1111-1138-6707) Findings: A total of 1,250 patients were randomised (623 intervention and 627 control) between 13 January 2014 and 12 February 2016. At six months, 285 of 607 (47·0%) participants in the intervention group were dead or dependent compared to 287 of 605 (47·4%) in the control group (odds ratio 0·98; 95% confidence Interval 0·78 to 1·23, P = 0·87). No significant differences were observed in any of the secondary or safety outcomes. Interpretation: Family-led rehabilitation did not reduce death or dependency after stroke.